0161 Development of an instrument assessing recovery expectations in patients receiving disability benefits secondary to mental health disorders. (23rd June 2014) - Ebrahim, Shanil; Malachowski, Cindy; Din, Mostafa Kamal el; Mulla, Sohail; Bance, Sheena; Montoya, Luis; Guyatt, Gordon; Busse, Jason
Abstract : Objectives: Of workers approved for long-term disability benefits, 31.6% suffer from a primary mental illness. Negative patient recovery expectations are associated with worse outcome in many conditions. Our objectives were: 1) to complete a systematic review to identify measures that assess patient recovery expectations, and 2) using the results from our review, develop an instrument designed to assess recovery expectations in individuals receiving disability benefits secondary to a mental health disorder. Method: We completed searches of MEDLINE and PSYCInfo from inception of each database to June 2013, to identify primary studies evaluating patient's recovery expectations across all clinical populations. Teams of reviewers completed title and abstract screening of citations, full text review of potentially eligible articles, data extraction, and quality assessment of eligible studies. Findings from the review and input from content experts informed the development of a comprehensive list of items that captured patient's recovery expectations. Results: We identified 12 599 unique citations; 46 studies were eligible. Studies reported on 20 different instruments assessing patient's recovery expectations. A minority (20%) of studies included measurement properties of reported instruments; 11% evaluated mental health conditions. No instruments were validated among patients receiving disability benefits or explored associations with return to work. Generalizability to disabled patients receiving wage replacement benefits is therefore unclear. Items that comprise our summary instrument will be presented at EPICOH. Conclusions: Our instrument holds promise for identifying claimants holding negative recovery expectations, which may be associated with prolonged recovery. These unhelpful beliefs may be a useful target for early interventional therapies.